IMPLEMENTASI PSAK NOMOR 46 ATAS PAJAK PENGHASILAN BADAN PADA LAPORAN KEUANGAN YAYASAN DEWI NATALIA KOTA MAKASSAR - Rosmayani Rosmayani; Dewi Natalia; Melisa Yanuar Susilo; Dina Utami; Andi Sutomo (Jurnal Ekonomi Ichsan Sidenreng Rappang, 2025)
This research was conducted by the author to determine the implementation of PSAK No. 46 on Corporate Income Tax in the financial statements of the Dewi Natalia Foundation in Makassar City. This research was conducted at the Dewi Natalia Foundation office in Makassar, a business entity engaged in education and social services. This study used a qualitative descriptive analysis method to uncover facts, circumstances, phenomena, variables, and conditions that occurred during the research period. The results indicate that the Dewi Natalia Foundation has not fully implemented PSAK No. 46 in its financial statements. In its income statement, the Dewi Natalia Foundation does not disclose or include deferred tax expense because management believes that the realization of this deferred tax is not yet certain.